IgG4-Related Perineural Disease. (18th March 2012) - Inoue, Dai; Zen, Yoh; Sato, Yasuharu; Abo, Hitoshi; Demachi, Hiroshi; Uchiyama, Akio; Gabata, Toshifumi; Matsui, Osamu
Abstract : Aims . To elucidate characteristics of IgG4-related disease involving the peripheral nervous system. Methods . Retrospective review of 106 patients with IgG4-related disease identified 21 peripheral nerve lesions in 7 patients. Clinicopathological and radiological features were examined. Results . Peripheral nerve lesions were commonly identified in orbital or paravertebral area, involving orbital (n = 9 ), optic (n = 4 ), spinal (n = 7 ), and great auricular nerves (n = 1 ). The predominant radiological feature was a distinct perineural soft tissue mass, ranging 8 to 30 mm in diameter. Histologically, the epineurium was preferentially involved by massive lymphoplasmacytic infiltration rich in IgG4 + plasma cells. All lesions were neurologically asymptomatic and steroid-responsive at the first presentation, but one recurrent lesion around the optic nerve caused failing vision. Conclusion . IgG4-related disease of the peripheral nervous system is characterized by orbital or paravertebral localization, perineural mass formation, and rare neurologic symptoms. The term "IgG4-related perineural disease" seems appropriate to describe this entity.